2011
DOI: 10.1007/s00251-011-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-binding lectin 1 haplotypes influence serum MBL-A concentration, complement activity, and milk production traits in Chinese Holstein cattle

Abstract: Mannose-binding lectin (MBL) is a member of the collectin protein family that binds a broad range of microorganisms and activates the lectin-complement pathway of innate immunity. MBL deficiency is associated with an increased risk for various infections and arises from five polymorphisms in the promoter and first exon of the MBL gene in humans. In this study, three novel single-nucleotide polymorphisms (SNPs) in the promoter region and two previously reported SNPs in exon 2 of the MBL1 gene were detected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 57 publications
1
20
2
6
Order By: Relevance
“…Beside sugars, MBL has also been found to bind to phospholipids, nucleic acids, and non-glycosylated proteins (Ip et al 2009). The MBL genes in human (Madsen et al 1994(Madsen et al , 1995Steffensen et al 2000;Sumiya et al 1991), porcine (Juul-Madsen et al 2011a;Lillie et al 2007), bovine (Liu et al 2011) and chickens (Kjaerup et al 2013) have been found to have polymorphisms resulting in wide variations in MBL serum levels in the organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Beside sugars, MBL has also been found to bind to phospholipids, nucleic acids, and non-glycosylated proteins (Ip et al 2009). The MBL genes in human (Madsen et al 1994(Madsen et al , 1995Steffensen et al 2000;Sumiya et al 1991), porcine (Juul-Madsen et al 2011a;Lillie et al 2007), bovine (Liu et al 2011) and chickens (Kjaerup et al 2013) have been found to have polymorphisms resulting in wide variations in MBL serum levels in the organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese Holstein cattle, polymorphism in the MBL1 gene has been found to influence MBL-A serum concentration, complement activity, and milk production traits. Also, results of correlation analysis suggest that the MBL1 gene is significantly correlated with cattle mastitis (Liu et al, 2011). In humans, three variant, coding MBL2 alleles with decreasing effect on MBL concentration in serum are known.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, SNPs in the exons and promoter regions of the JAK2 and STAT5B genes can change the RNA stability of their target genes (Liu et al . ). In our initial work, a total three SNPs, including those in intron 4, exon16 and exon 19, were identified in bovine STAT5B .…”
Section: Discussionmentioning
confidence: 97%